SOSIALISASI DAN EDUKASI PEMBUATAN MINUMAN SERBUK INSTAN JAHE MERAH UNTUK KESEHATAN DI SMK NEGERI 1 PATUMBAK - Harnis, Zola Efa; Saberlan, Jhan Saberlan; Facrunisa, Dian (INSTITUT KESEHATAN DELI HUSADA, 2024)
Red Ginger (Zingiber Officinale var Rubrum) is one of the plants of the Zingiberaceae tribe which plays a role in its use as a drink or food mixture. The metabolite content of red ginger is useful for herbal drinks, cooking ingredients and herbal medicines. Red ginger can also be used to treat various diseases such as flu, relieve nausea in pregnant women, rheumatism, aches, sore throat disorders, colds. In using red ginger as a drink, the aspect that is an obstacle to the use of this rhizome is that it takes quite a long time to make the drink so there is a tendency for people to be lazy about making it. Instant ginger drink can be enjoyed at any time and is practical to make. Instant red ginger is in the form of a drink combined with sugar through a manufacturing process that is quite easy and practical to implement.